Development and optimisation of a reception testing protocol designed to eliminate HCV in the UK prison population - Emily Mongale; Samantha Allen; Iain Brew; Arran Ludlow-Rhodes; Nichola Royal; Julia Waldron; Hannah Alexander; Lee Christensen; Kate Dorrington; Andrew Milner; Louise Missen; Andy Jones; et al. (JHEP Reports, 2024)
Background & Aims: Micro-elimination of hepatitis C virus (HCV) in high-risk populations is a feasible approach towards achieving the World Health Organization’s targets for viral hepatitis elimination by 2030. Prisons represent an area of high HCV prevalence and so initiatives that improve testing and treatment of residents are needed to eliminate HCV from prisons. This initiative aimed to improve the HCV screening and treatment rates of new residents arriving at prisons in England. Methods: A rapid test and treat pathway was developed and implemented in 47 prisons in England between May 2019 and October 2021 as a healthcare service improvement initiative. Prison healthcare staff performed opt-out HCV testing for all new residents at each prison within 7 days of arrival, and those who were positive for HCV RNA were offered treatment with direct-acting antivirals (DAAs). The Hepatitis C Trust provided peer support for all residents on treatment and those who were released into the community. Results: Of 107,260 new arrivals, 98,882 (92.2%) were offered HCV antibody testing, 63,137 (63.9%) were tested and 1,848 were treated. Testing rates increased from 53.7% in Year 1 to 86.0% in Year 3. Between May 2020 and October 2021, 40,727 residents were tested, 2,286 residents were positive for HCV antibodies and 940 residents were HCV RNA positive, giving an antibody prevalence of 5.6% and an RNA prevalence of 2.3%. A total of 921 residents were referred for treatment and 915 initiated DAA treatment (97.3% of whom were HCV RNA positive). Conclusions: This initiative showed that an opt-out HCV test and treat initiative in prison receptions is feasible and can be adapted to the needs of individual prisons as a viable way to achieve HCV micro-elimination. Impact and implications: Prisons represent an area of high HCV prevalence and so initiatives that improve testing and treatment of residents are needed to eliminate HCV from prisons. The reception testing protocol improved HCV screening in new arrivals across 47 prisons in England and could be a viable way for countries to achieve HCV micro-elimination in their prison systems. The reception testing protocol presented here can be adapted to the individual needs of prisons, globally, to improve HCV screening and treatment in this setting.